AN APPROACH TO VISUALIZATION OF MULTIVARIATE SCENARIO FORECASTS OF THE MAIN ECONOMIC INDICATORS OF A PRODUCTION ENTERPRISE - I. E. Perminova (Цифровая трансформация, 2018)
The article substantiates a methodical approach to visualization of forecast data and construc-tion of the upper component of the BPM-complex – information panel. In software implementation of predictive calculations under risk conditions, access to the SAP Business Warehouse repository is performed several times: when creating a model database with the purpose of the initial information aggregation, and after carrying out model calculations on the dashboard and analytics, when KPI values are reached. This method was implemented on LTD «Minsk Margarine Factory». Implementation of the method on real data showed the possibility of prompt selection of controls in the interactive mode with the output to target KPI-indicators, which ensures the imple-mentation of the feedback principle of the system (OLAP and OLTP levels) without using a com-plex mathematical apparatus.